ASPECTS REGARDING THE SIMULATION OF THE OPERATION OF THE CONTROL PART FOR A THREE-PHASE VOLTAGE INVERTER USING OPEN SOURCE SOFTWARE TOOLS (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
In this paper, a series of aspects regarding the simulation of the control part related to a three-phase voltage source inverter with PWM modulation are presented. The simulations were performed using an open source software. The advantage of using this type of software is related to the fact that fast simulations can be performed, results can be validated, analyzes can be made, without the need to use commercial software tools.
Keywords: three phase inverter; circuit simulation; open source software; PWM control